KF-1 ubiquitin ligase: an anxiety suppressor - Hashimoto-Gotoh, Tamotsu; Iwabe, Naoyuki; Tsujimura, Atsushi; Takao, Keizo; Miyakawa, Tsuyoshi (Frontiers in Neuroscience, 2009)
Anxiety is an instinct that may have developed to promote adaptive survival by evading unnecessary danger. However, excessive anxiety is disruptive and can be a basic disorder of other psychiatric diseases such as depression. The KF-1, a ubiquitin ligase located to the endoplasmic reticulum (ER), may prevent excessive anxiety; kf-1−/− mice exhibit selectively elevated anxiety-like behavior against light or heights. Thus, KF-1 may degrade some target proteins, responsible for promoting anxiety, through the ER-associated degradation pathway, similar to Parkin in Parkinson's disease (PD). Parkin, another ER-ubiquitin ligase, prevents the degeneration of dopaminergic neurons by degrading the target proteins responsible for PD. Molecular phylogenetic studies have revealed that the prototype of kf-1 appeared in the very early phase of animal evolution but was lost, unlike parkin, in the lineage leading up to Drosophila. Therefore, kf-1−/− mice, be a powerful tool for elucidating the molecular mechanisms involved in emotional regulation, and for screening novel anxiolytic/antidepressant compounds.